2014
DOI: 10.1002/app.40888
|View full text |Cite
|
Sign up to set email alerts
|

Toughening of poly(lactic acid) with the renewable bioplastic poly(trimethylene malonate)

Abstract: The aim of this work was to enhance poly(lactic acid)'s (PLA) flexibility and ductility by blending it with another bioplastic. Poly(trimethylene malonate) (PTM), developed as part of this study, was synthesized from 1,3-propane diol and malonic acid via melt polycondensation. Blend films of PLA and PTM were prepared by solvent casting from chloroform. Differential scanning calorimetry and thermogravimetric analysis were used to show shifted phase transitions and a single glass-transition temperature, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…DSC analysis revealed that it presents T g at −57 °C and a endothermic event associated to T m at 32 °C. The T g value is in agreement with a T g reported in the literature by Eyiler for a poly(trimethylene malonate), but no mention of T m is made. Our results suggested that this low molecular weight trimethylene malonate can present a certain X c .…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…DSC analysis revealed that it presents T g at −57 °C and a endothermic event associated to T m at 32 °C. The T g value is in agreement with a T g reported in the literature by Eyiler for a poly(trimethylene malonate), but no mention of T m is made. Our results suggested that this low molecular weight trimethylene malonate can present a certain X c .…”
Section: Resultssupporting
confidence: 88%
“…We have found in the literature a previous work on blends of high molecular weight poly(trimethylene malonate) and PLA in which immiscibility was reported . In the present work we use a relatively low molecular weight oligomer based on these two bio‐based monomers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blending polymers with low molecular weight plasticizers has been one of the most effective approaches to improve processability, flexibility, ductility, and toughness of polymers . In our previous study, the blending of PTM with poly(lactic acid) (PLA) led to significant toughness improvement and easier processing due to lower viscosity, making PLA suitable for commercial applications . In this article, we present the synthesis and characterization of a linear bio‐based polymer, poly(trimethylene malonate) (PTM) and a branched, unsaturated bio‐based polymer, poly(trimethylene itaconate) (PTI) with bimodal molecular weight distribution via melt polycondensation by following green chemistry principles.…”
Section: Introductionmentioning
confidence: 99%
“…With the considerably improved environmental awareness of society and concerns about the depletion of petrochemical based plastics, biodegradable plastic materials derived from renewable resources have attracted a great deal of attention. 1,2 As a typical kind of bioplastics, polyhydroxyalkanoates (PHAs) are synthesized and accumulated as intracellular carbon and energy storage material by many bacteria. 3,4 Owing to the outstanding properties, such as biodegradability, biocompatibility, excellent mechanical performance comparable with traditional petroleum-based plastics like polypropylene/(PP) and polyethylene/(PE), 5 PHAs have wide application prospects in the industrial, medical and agricultural fields.…”
Section: Introductionmentioning
confidence: 99%